Empresa e família: instituições que se entretecem na continuidade de uma cultura organizacional - Silva, Roseane Grossi (2010)
Understanding enterprise and performing actions to achieve the desired goals is to unravel the rules, customs, habits, social rules, dreams, emotions and meanings that constitute it. It is to recognize that economic rationality is intertwined with subjectivity, ultimately. It is to understand the individuals and the relationships they build their organizational culture. Interpreting the culture of an organization is to recognize the ambiguities arising from experiences that are unique to each individual who composes it and cannot be given a concept that refers only to homogeneity. The culture is heterogeneous, composed simultaneously by consensus, clarity and consistency of events. It is formed by the differences, making subcultures and it is ambiguous in that consensus, clarity and consistency exist in certain circumstances, being ephemeral.In a family business functions and activities of the company are fostered by relatives. The enterprise starts the process of growth and there are multiple challenging and limiting factors to their continuity, allowing or not that the business can persist over generations and by time developing activities toward the future and achieving long-term success. Organizational culture may be indicated as a factor taxpayer of the continuity of family businesses, emerging from the need to understand which would be the events in those companies that interfere in its perpetuity. Therefore, the aim of this study is to answer as the cultural events, from the standpoint of integration, differentiation and fragmentation of a family organization at Uberlandia, act limiting and/or enabling its continuity? The study has a qualitative approach and it is descriptive. The method of procedure used was based in ethnography. The case study was used as a strategy to reach the proposed objective. As regards to techniques for data collection were used non-participant observation, participant observation and search for documents focusing on five categories: How Things Work, The jokes that people make; Adequacy of Physical Structure and Equipment, Remuneration Policy and Relationships Among Pairs and Other Groups. For data interpretation, a content analysis and discourse analysis were performed. The choice of object was caused by information that characterized the enterprise declaredly a family organization. It was noted that the marked influence of organizational culture in the universe of these enterprises as well as revealed characteristics associated with cultural events which unveiled topics allowing the enrichment of literature and contributing to studies on family businesses. The presence of an organizational culture from the perspective of integration, differentiation and comminution could be verified. At the same time the culture had demonstrations that can enable its continuity. Other events that go against them, limiting perpetuity, were found. Or due to interweaving of family and business, that permeates the culture of the organization, constantly linking the two institutions, there is the presence of events, which limit both its continuity as possible, simultaneously. It was noted that relative influence not only is one of these enterprises but also is essential, directing and motivating the harmony of the organizational system